2014
DOI: 10.1111/dsu.12433
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Sebaceous Carcinoma and Early Outcomes of Treatment Using Mohs Micrographic Surgery Versus Wide Local Excision: An Update of the Mayo Clinic Experience Over the Past 2 Decades

Abstract: MMS and WLE are effective treatments for SC. Further research is warranted to determine whether one treatment is more efficacious than the other.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 27 publications
2
21
1
1
Order By: Relevance
“…Mohs micrographic surgery and wide local excision were equally effective in terms of outcomes, and either could therefore be pursued in the organ transplant population. This is consistent with a previous study in nontransplant recipi‐ents, in which Mohs micrographic surgery and wide local excision were equally effective …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Mohs micrographic surgery and wide local excision were equally effective in terms of outcomes, and either could therefore be pursued in the organ transplant population. This is consistent with a previous study in nontransplant recipi‐ents, in which Mohs micrographic surgery and wide local excision were equally effective …”
Section: Discussionsupporting
confidence: 93%
“…We found 50% of the tumors tested to have microsatellite instability; none of these patients, however, were exposed to azathioprine. While a previous study proposed that azathioprine may interact with DNA MMR proteins and lead to microsatellite instability, this was not seen in our one tumor from a patient exposed to azathioprine . In our three cases that had microsatellite instability, it is possible that tacrolimus or mycophenolate mofetil could be interacting with the MMR proteins.…”
Section: Discussioncontrasting
confidence: 72%
“…Recently, staining for the androgen receptor was reported to be useful in diagnosing SC (39). Further studies using immunohistochemistry are warranted in Korea.…”
Section: Discussionmentioning
confidence: 99%
“…A surgical margin of 5–6-mm in WLE is commonly recommended for SCs, and a 2-mm margin in MMS has been reported to be effective (40). Although more studies comparing the long-term outcomes of MMS vs. WLE are necessary, MMS is recognized as the best initial treatment modality for SC (39). Both WLE and initial MMS in our study showed excellent results.…”
Section: Discussionmentioning
confidence: 99%
“…Leaving no residual cancer cells at the cutting edge is the key to success. Moreover, the recurrence is positively correlated with the tumor size, so an early diagnosis is important for the prognosis of a sebaceous gland carcinoma [24,25] . Because there is limited research on the ocular type of sebaceous gland carcinoma, there is no specific diagnosis and treatment for a mature teratoma with a malignant transformation.…”
Section: Yun-xiao Zhou Et Al 24mentioning
confidence: 99%